(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s
(3ChdgG (B:s
(3ai JbSje GdeOGhGI hWQb GdYdGL ai GeJMGf GdOhGA ef GdJLQHI Ydi GdGHOGf ,ai GeJMGf GdOhGA ef SQYI GSJLGHJg s
(3BNQgG (B:s
(3aQGjJ Gf GHjf hGTQM ai GdMGd ai cd hGMO efgG heG jMOKg ef GdBaI ai GdHOf ,heG jTai ef Jdc GdBaI s
(3bWYI KGfjI JTJed Ydi GdebGdI GdKGfjI ef GdLRA GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B153 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
Keywords: (3GdWHs